Social fitness and resilience : a review of relevant constructs, measures, and links to well-being - McGene, Juliana (RAND project AIR FORCE series on resiliency. Social fitness and resilience, 2013)
Examines social fitness, the combination of resources from social connections that influence how individuals respond to stressful circumstances, to identify methods of increasing social connectedness and support among U.S. Airmen and their families.